Numerical Investigation of the Two-Dimensional Fredholm Integral Equations of the Second Kind by Bernstein Operators - Iyikal, Ovgu Cidar (Mdpi, 2022)
In this study, the numerical solutions of linear two-dimensional Fredholm integral equations of the second kind via Bernstein operators are considered. The method is presented with illustrative examples for regularized-equal and Chebyshev collocation points. The obtained numerical results from illustrative examples show that the proposed numerical algorithm is accurate and efficient for solving linear two-dimensional Fredholm integral equation of the second kind.
Keywords: Fredholm integral equations; Bernstein approximation; Chebyshev collocation points